Misturatosphaeria viridibrunnea sp. nov. (Teichosporaceae, Pleosporales) from Thailand - Boonmee, Saranyaphat; Wijayawardene, Nalin N.; Bhat, D. Jayarama; Tennakoon, Danushka S.; Hyde, Kevin D. (Phytotaxa, 2019)
We introduce a new species, Misturatosphaeria viridibrunnea, isolated from dead branches of an unidentified terrestrial dicotyledonous plant in Chiang Rai, Thailand. The new species is characterized by fusiform, 1-septate, olivaceous brown to dark brown, regularly 4-guttulate ascospores with slightly longitudinal striations on surface. Misturatosphaeria viridibrunnea is easily distinguishable from other species in the genus by smaller-sized ascomata, asci and ascospores. Phylogenetic analyses using a combined gene analysis of LSU and ITS sequence data indicated that the new species belongs to Teichosporaceae (Pleosporales). A detailed morphological description and illustration of the new species is provided.